Uncertainty Assessment of Alpha-Spectrometry Analysis of 210Po in Marine Sediment Sample from Jakarta Bay - Ali Arman Lubis (Institut Teknologi Bandung, 2008)
The expression of measurement uncertainties in a standardized form is a requirement for result reliability as it imposesimplications to the interpretation of analytical results. In this work, the analytical procedure involves samplepreparation steps for drying, dissolution and further radiochemical separation, self deposition and counting of 210Po ofmarine sediment sample are discussed. An isotopic tracer (209Po) is used to determine the overall chemical yield and toensure traceability to a national standard. The uncertainty assessment of 210Po is discussed using marine sedimentsample from Jakarta Bay with quality assurance based on Standard Reference Material, International Atomic EnergyAgency, No. 300 (SRM IAEA-300) and SRM IAEA-368 for marine sediments. 210Po is measured by a PIPS detectorcoupled to a multichannel spectrometer. The contribution of the sources to the expanded standard uncertainty in theconcentration of 210Po in marine sediment is assessed and the sample activity which contributed 71.10% of total isidentified as the major contribution.